Corporate sustainability performance across economic development countries: a systematic literature review on the innovation to achievement - Marlina, Eka; Abdinagoro, Sri Bramantoro (Frontiers in Sustainability, 2026)
The trend of sustainability in the industrial world has intensified, particularly since the COVID-19 pandemic, when public awareness of personal health, environmental preservation, and planetary sustainability rose sharply, signaling a rapid shift in societal mindset driven by technological advancement. The industrial sector has adapted to this shift, recognizing that markets increasingly favor products with sustainability value, while pricing remains crucial for profitability and government regulations play a significant external role. Business growth and environmental sustainability have thus evolved into a holistic concern, where sustainable development, meeting present needs without compromising future generations, has become a strategic objective. This study employs a Systematic Literature Review (SLR) using the PRISMA methodology, analyzing 236 peer-reviewed publications from 2015 to 2025 indexed in Scopus (Q1–Q4), and classifying research themes based on corporate strategies for achieving sustainability performance across countries with differing economic development levels. Research problem of this study is centered on how economic development influences corporate sustainability performance, and the findings reveal both the progress and challenges faced by companies in different economic contexts. The findings reveal that integrating sustainability into corporate strategy significantly enhances long-term performance and competitiveness; stakeholder engagement and innovation act as mediating factors strengthening sustainability outcomes; and institutional pressures, including regulations and social norms, accelerate the adoption of sustainability-oriented practices. The study highlights that Corporate Sustainability Performance (CSP) research and adoption surged, particularly in developed nations, reflecting a global shift towards integrating environmental, social, and economic factors for long-term success. However, a significant gap persists in developing countries like Indonesia, where despite growing reporting, challenges such as inconsistent regulations and limited SME awareness hinder effective integration, underscoring the urgent need for targeted policies and research in these regions to achieve holistic sustainability.